Endovascular treatment of arterio-ureteral fistulae with covered stents: Case series and review of the literature. (28th August 2014) - Patel, Dhruv; Kumar, Abhishek; Ranganath, Praveen; Contractor, Sohail
Arterio-ureteral fistulae are abnormal connections between an artery and the ureter and carry a high mortality. We present two cases of arterio-ureteral fistulae that presented with life-threatening hematuria. Both patients were treated with endovascular covered stent placement.